The Effect of Using Interactive Multimedia to Upgrade Students' Listening Comprehension of 1st Semester Students of English Department at UNISMA - Harwinda Hasim (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The research was aimed to improve students listening comprehension using interactive multimedia in first semester students of English department at UNISMA. This research used Quasi-Experimental Design. The data were gathered from the tests (pre-test and post-test) with the participants. The participants of this research were two classes with the total students were 56 students from English Department at UNISMA and they were divided into experimental class and control class. The results of this research showed that there are no significant differences between students who were taught by using interactive multimedia with the students who were taught by using a traditional method. It showed from the result of the pre-test and post-test in the experiment class and control class. The significant value on the test shows that there is no significant difference. Finally, the researcher expected that the result will help future researcher who want to conduct this similar study to use more attractive videos, audios, and texts in teaching listening using interactive multimedia. Key Words: interactive multimedia, listening comprehension